New species of Haliclona (Demospongiae: Haplosclerida: Chalinidae) from Western Australia - Fromont, Jane; Abdo, David A. (Zootaxa, 2014)
Two new sponge species, Haliclona durdong sp. nov. and Haliclona djeedara sp. nov. from the south west of Western Australia are described. Morphologically distinct from each other, both species are assigned to the genus Haliclona subgenus Haliclona. Haliclona djeedara sp. nov. individuals are ficiform to lobate, brown to beige in colour and have numerous apical oscules. Haliclona durdong sp. nov. individuals have a massive morphology, green colour, and large funnel-like oscules. The description of these two new species brings the species of Haliclona (Haliclona) in Australia to 25.